Optimization process of binahong extraction and characterization study - Sri Murni, Astuti (2011)
Binahong is Anredera cordifolia (Ten) Steenis is including ones a medicinal plant and being used as herbal medicine. These compounds include saponin and polyphenols. They involve a lot of activities, one of these is the antimicrobial activity that will be used to treat infectious diseases by microorganism agents, resistance by microorganisms produce. However, the compound of Binahong plant is not well documented and scientific evidence is limited to establish as medicinal plant. The research proposed to know optimization process of Binahong extraction and characterization study. The samples are leaves, tuber, stems, flower and local capsule of Binahong carried out optimization processing of Total Phenol Content (TPC) by using UV Vis-Spectrophotometer and tetracycline activity (TCA) by bioassay. The optimization extraction of processes was evaluated with the aid of Design Expert version 6.0.8 using response surface methodology (RSM). The characterization of TPC and TFC by using UV Vis-Spectrophotometer, the antibiotic activity analysed by bioassay, the bioactive compounds from a volatile oil compound analysed by using GCMS, and accumulation of heavy metals on Binahong plant analysed by Inductively Coupled Plasma Mass Spectrometer (ICPMS). The results of TPC in leaves were optimum temperature at 65OC and concentration between 45 mg/l to 62.5 mg/l, in actual factor time 17.50 minutes. While the point optimum of tetracycline activity (TCA) from tuber, at temperature 72.50 OC for time 32.50 minute. The phenolic and flavonoid compound were higher in flower extract, then leaves and tuber. For the local capsule of Binahong was higher than leaves and tuber. The result of compounds analysed by using GC-MS were 68 kind of compounds. The heavy metals result were found Mg (38.80 ± 0.10) ppm; Cu (1.542 ± 0.01) ppm; Se (0.023 ± 0.002) ppm and Zn (7.310 ± 0.02) ppm, but in tuber was Mg (10.10 ± 0.02) ppm, Cu (0.652 ± 0.01) ppm, Se (<1.636 ± 0.003) ppm and Zn: 2.729 ± 0.01) ppm. However, from contamination of heavy metal such as in the leaves, As (0.008 ± 0.01) ppm, Cd (0.003 ± 0.02) ppm, Pb (0.0629 ± 0.03) ppm and Cr: (0.098 ± 0.01) ppm. While from a tuber was: As (< 0.017 ± 0.01) ppm, Cd (< 0.015 ± 0.03) ppm, Pb (0.0091 ± 0.02) ppm and Cr 0.036 ± 0.03 ppm. The Binahong plant as medicinal herbal has the high antioxidant activity such as total phenolic, flavonoid and saponin compound. The plant is also contained group of fatty acid, phytosterol, tocopherol, polyphenols, phytol and antibiotic activity. The Binahong plant was safe for humans consumption and has a lot of benefit for human health